Pengujian Perangkat Lunak Berstandar ISO/IEC 29119 pada Website Literasi Digital "SukaBaca" - Nasmilzha Gusfiarta Rachmadi; Akmal Febrian; Chairul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The advancement of information technology in education encourages the use of web-based literacy systems to support teaching and learning activities. SukaBaca is an online literacy platform that provides class management, reading materials, and quiz features accessed through a class code mechanism. This study aims to evaluate the functional quality of the SukaBaca website using the ISO/IEC 29119 standard through the Software Testing Life Cycle (STLC) approach. Black-box testing was applied to core features, including user authentication, class and material management, quizzes, and score calculation. The results indicate the presence of several functional bugs that affect user experience, highlighting the need for further system improvements.